Design Android Applications My Mind Mapping (M3) Physical Education, Sport, & Health Subject Curriculum 2013 for Teachers Guidance Xth Grade Vocational High School (Journal of Physical Education and Sports, 2018)
The android app on the smartphone makes it easy for a user to communicate and get access to various information. The purpose of this research is to design an android based application in the form of mind mapping. This application is a form of transformation from the manual form (book, e-book, module, etc.) to digital form in the form of an application containing Core Competence & Basic Competence, materials, and learning model for teacher guidance of Physical Education, Sport, & Health Subject Xth grade Vocational High School. This research uses ADDIE model which includes analysis, design, development, implementation, and evaluation. The results of the product trial at first stage curriculum experts with the average score of 3.4 (67%) included the "adequate" category and second stage with the average score of 4.5 (90%) including the "excellent" category. The trial of the product at first stage multimedia / IT expert with an average score of 3.4 (68%) included the "adequate" category and second stage with an average score of 4.5 (89%) included in the "excellent" category. The test of product effectiveness on a small scale with an average rating of 4.24 (84.7%) was rated "excellent". The test of product effectiveness on a large scale with an average rating of 4.18 (83.5%) is categorized as "excellent". Conclusion, that the android application product My Mind Mapping (M3) Physical Education, Sport, & Health Subject Curriculum 2013 is effective used for teacher guidance Xth grade Vocational High School.